Sosialisasi Pengembangan Sistem Pengajuan Cuti Online Pegawai di Rumah Sakit Umum Anwar Medika Sidoarjo - Yusmanisari, Eka; Nanda Pratiwi, Tiara Suci; Febrianti, Nur Andini; Fikriah, Sahilatul; Dewi, Rhosita; Sakdiyah, Redita Halimatus; Azmi, Ulul (Jurnal Abdimas Jatibara, 2023)
The employee leave system at Anwar Medika Sidoarjo General Hospital is still done manually, using documents that do not have a special database. This certainly affects the effectiveness and efficiency of work because officers must input employee leave applications every day. By implementing the online employee leave application, it is expected that officers in the personnel department will be able to work more effectively there by increasing the performance of officers. The output of this stage is the need for the hospital, namely educating employees about the procedures for using the online leave application so that the application can be implemented at the hospital. The number of employees at Anwar Medika General Hospital is approximately 788 employees with leave still being carried out manually and still have to ask for signatures from related parties as proof of approval for submitting leave which requires time and accuracy in checking data. In the era of digitalization, hospitals should implement online-based leave for employees so they don't have trouble in terms of leave. The results achieved are that employees are able to apply the application smoothly, safely, precisely and comfortably in accordance with the procedures that have been given.